The trunk is exploited for energy transfers of maximal instep soccer kick: A power flow study - da Silva Carvalho, D.; Melo Ocarinoa, J.; de Castro Cruz, A.; Drumond Barsante, L.; Gonçalves Teixeira, B.; Alves Resende, R.; Teixeira Fonseca, S.; Rezende Souza, T. (Journal of Biomechanics, 2021)
The purpose of this study was to investigate the angular kinetic energy transfers and expenditure among the trunk (bisegmented), the pelvis and the kick limb during maximal soccer instep kicking, and to characterize kicking kinetics and kinematics. Eighteen adult male amateur soccer players (24.0 ± 4.1 years old) were assessed. Three-dimensional kinematics and ground reaction force were measured. A 6-degrees-of-freedom model was assumed, comprising the upper trunk, lower trunk, pelvis, thigh, shank and foot, and the thoraco-lumbar, lumbo-pelvic, hip, knee, and ankle joints. Angular kinematics and joint moments were computed. Power flow analysis was done by calculating the joint powers (to describe joint-to-segments energy transfers) and the proximal and distal segment powers (to describe segment-to-segment transfers). Power, kinematic and kinetic time series were presented to describe the energy flows` directions. The total mechanical energy expenditure (TMEE) at each joint was also calculated. The TMEEs pointed to substantial energy expenditure at the trunk (27% of the summed work produced by the analyzed joints). In the initial phases of kicking, the trunk generates downward energy flows from the upper to the lower trunk and from the lower trunk to the pelvis, and then to the lower limb, sequentially, which favors angular motions for ball contact. There is a formation and release of a tension arc only at the hip joint, and deceleration of the segments slightly sooner than ball contact, differently from theoretical accounts. There are energy flows, hitherto unknown, among the trunk, pelvis and kick limb, revealing mechanical strategies of kicking.